Does Annual Report Readability Reveal Business Strategy and Earnings Management? - Salma Lathifah Salsabila; Fitriasari, Rizka (Reviu Akuntansi, Keuangan, dan Sistem Informasi, 2023)
His study aims to provide empirical evidence of the effect of business strategy and earnings management on the readability of the annual report information of all non-financial public companies listed on the Indonesia Stock Exchange (IDX) between 2019 and 2021. The samples include 344 companies selected through non-probability sampling with purposive sampling, and the data are analyzed by multiple linear regression model utilizing SPSS 26 data processing software. The results of this study exhibit that the company's business strategy affects the readability of the annual report information disclosure. However, this study cannot find evidence that the annual report information readability is related to company accrual earnings management. The readability of the company's yearly report information disclosure is likely to be driven by the company's business characteristics. Abstrak Penelitian ini bertujuan untuk mengetahui pengaruh auditor switching, audit complexity, dan firm size terhadap audit report lag. Objek penelitian yang diteliti adalah perusahaan sektor properties & real estate yang terdaftar di Bursa Efek Indonesia tahun 2019-2021. Teknik pengambilan sampel dalam penelitian ini adalah purposive sampling dengan sampel sebanyak 144 entitas yang memenuhi kriteria penelitian selama periode 2019-2021 dari 226 entitas yang ada. Penelitian ini menggunakan analisis model regresi linier berganda dengan program pengolahan data Statistical Product and Service Solution (SPSS) versi 26 dalam menguji hipotesis. Hasil penelitian ini menujukkan bahwa auditor switching dan firm size secara signifikan berpengaruh terhadap audit report lag, sedangkan audit complexity tidak signifikan berpengaruh terhadap audit report lag.